Magic and Popular Religion : Symbolic Tools for Empowering the Subalterns - Borjan, Etami (Array, 2012)
The most prominent Italian anthropologist Ernesto De Martino became known internationally owing primarily to his study of the “magical” phenomena in southern Italy such as mourning rituals, trance, possession, and “tarantism” . The main focus of his research was the role that magic had in the formation and maintenance of social order in pre-modern and pre-industrial societies. De Martino’s research in southern Italian regions highlighted controversies and ambiguities in the post-Second World War Italy. Mystic phenomena found in the South stressed social and political diversities within the country that was struggling to build a sense of national unity and identity among its culturally, linguistically, and historically disunited inhabitants. Besides revealing how much unknown was the Italian South within its national as well as European borders, De Martino’s scholarship has influenced Italian and European cultural anthropology to approach the role of religion and rites with political commitment.